2020
DOI: 10.1002/marc.202000080
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Polymeric Radicals: Highly Promoted Formation and Stabilization of Naphthalenediimide Radical Anions

Abstract: The supramolecular polymeric radicals are developed to promote the generation efficiency and stability of naphthalenediimide (NDI) radical anions. To this end, a water‐soluble bifunctional monomer bearing two naphthalene‐viologen end groups and a NDI center is designed and synthesized. The supramolecular polymeric NDI radical anions are fabricated on the basis of host–guest complexation between the NDI‐containing bifunctional monomer and cucurbit[8]uril (CB[8]) and followed by the photoinduced electron transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…S20 (ESI†), the diffusion coefficient of L4/0.67SDS was slightly larger than that of the L4/0.67SDS/0.67CB[8] mixture ( D L4/0.67SDS = 2.00 × 10 −10 m 2 s −1 , D L4/0.67SDS/0.67CB[8] = 1.62 × 10 −10 m 2 s −1 ), indicating that the introduction of CB[8] interacting with the remaining free viologen in L4/0.67SDS changed the state of the original assembly and led to the formation of larger assemblies. 64 In addition, we investigated the time-dependent morphological changes of binary and ternary supramolecules by TEM characterization. It was found that the change morphological trajectories of L4/0.67SDS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S20 (ESI†), the diffusion coefficient of L4/0.67SDS was slightly larger than that of the L4/0.67SDS/0.67CB[8] mixture ( D L4/0.67SDS = 2.00 × 10 −10 m 2 s −1 , D L4/0.67SDS/0.67CB[8] = 1.62 × 10 −10 m 2 s −1 ), indicating that the introduction of CB[8] interacting with the remaining free viologen in L4/0.67SDS changed the state of the original assembly and led to the formation of larger assemblies. 64 In addition, we investigated the time-dependent morphological changes of binary and ternary supramolecules by TEM characterization. It was found that the change morphological trajectories of L4/0.67SDS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A cucurbit[8]­uril (Q[8] or CB[8]) host is a larger homologue of the Q­[ n ]­s family, which not only can accommodate and stabilize V •+ radicals in the confined cavity , but also distinguishes itself by encapsulating V 2+ derivative guests as the electron-accepting moiety and an electron-donating guest to form a host-enhanced charge-transfer complex in its rigid space. In addition, Q[8] as the host can also simultaneously include two homo guests, such as arylpyridinium or naphthalene, which can be dimerized inside the cavity to form highly stable Q[8]-enhanced π–π complexes under the macrocyclic confinement effect. , Evidently, these results indicate that the confined space of the Q[8] cavity has the excellent advantages of strengthening the weak intermolecular interactions and controlling the orientation of the two encapsulated guests. However, to the best of our knowledge, V •+ radicals that are directly triggered by the Q[8]-confined space via intermolecular PET have not yet been studied …”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, V •+ radicals that are directly triggered by the Q [8]-confined space via intermolecular PET have not yet been studied. 32 In this work, as a proof-of-concept model, N,N′-bis(4carboxylphenyl)-4,4′-bipyridinium (BcpV 2+ 2Cl − ) was designed as the guest to bind with the Q [8] host (Scheme 1a). As shown in Scheme 1b, Q [8] could trigger the BcpV 2+ guest to form linear J-type polymers by simultaneously accommodating two terminal carboxylphenyl groups of the guest in its cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CB[ n ]s have been widely used in radical chemistry, such as regulating the generation of radicals, [ 11 ] enhancing the stability of radicals, [ 12 ] improving the catalytic activity of free radicals, [ 13 ] and constructing responsive materials. [ 14 ] However, reports on using CB[ n ]s to regulate the generation of free radicals from water‐soluble thermal initiators were lacking.…”
Section: Background and Originality Contentmentioning
confidence: 99%